129I/127I and Δ14C records in a modern coral from Rowley Shoals off northwestern Australia reflect the 20th-century human nuclear activities and ocean/atmosphere circulations. (September 2021) - Mitsuguchi, Takehiro; Okabe, Nobuaki; Yokoyama, Yusuke; Yoneda, Minoru; Shibata, Yasuyuki; Fujita, Natsuko; Watanabe, Takahiro; Saito-Kokubu, Yoko
Abstract: Radionuclides produced by 20th-century human nuclear activities from 1945 (e.g., atmospheric nuclear explosions and nuclear-fuel reprocessing) made significant impacts on earth's surface environments. Long-lived shallow-water corals living in tropical/subtropical seas incorporate the anthropogenically-produced radionuclides, including 129 I and 14 C, into their skeletons, and provide time series records of the impacts of nuclear activities. Here, we present 129 I/ 127 I and Δ 14 C time series records of an annually-banded modern coral skeleton from Rowley Shoals, off the northwestern coast of Australia, in the far eastern Indian Ocean. The 129 I/ 127 I and Δ 14 C records, covering the period 1930s−1990s, exhibit distinct increases caused by the nuclear activities, and their increasing profiles are clearly different from each other. The first distinct 129 I/ 127 I increase occurs from 1955 to 1959, followed by a decrease in 1960–1963. The increase is probably due to US atmospheric nuclear explosions in Bikini and Eniwetok Atolls in 1954, 1956 and 1958. The 129 I produced in those nuclear tests would be transported by the North Equatorial Current, a portion of which passes through the Indonesian Throughflow and then reaches Rowley Shoals. This initial increase from 1955 is, however, absent in the Δ 14 C record, which shows a distinct increase from 1959 and its peak around the mid-1970s, followed by a gradual decrease. This absence and the 4-year-delayed Δ 14 C increase are likely due to dilution of explosion-produced 14 C with natural carbon (by seawater mixing and air-sea gas exchange) being much more intense than that of explosion-produced 129 I with natural iodine (by the same processes), suggesting that the 129 I/ 127 I ratio is a more conservative anthropogenic tracer in surface ocean waters, as compared to Δ 14 C. The second 129 I/ 127 I increase is contemporaneous with a rapid Δ 14 C increase during 1964–1967, followed by a rapid 129 I/ 127 I decrease in 1968–1969; the increases can be ascribed to very large atmospheric nuclear explosions conducted in the former Soviet Union in 1961–1962. The third 129 I/ 127 I increase appears between 1969/1970 and 1992, which can be attributed to airborne 129 I released from nuclear-fuel reprocessing facilities in Europe, the former Soviet Union and the US. The coral 129 I/ 127 I and Δ 14 C time series records, combined with previous studies, enhance our understanding of the behavior of anthropogenic 129 I and 14 C in the global ocean and atmosphere. Highlights: 129 I/ 127 I and Δ 14 C data of modern coral annual bands in Rowley Shoals are presented. Natural (non-anthropogenic) 129 I/ 127 I and Δ 14 C levels in Rowley Shoals are evaluated. 129 I from the US Pacific bomb tests was conveyed to Rowley Shoals by ocean currents. 129 I is more conservative than 14 C, as an anthropogenic tracer of ocean currents. Airborne 129 I from nuclear-fuel reprocessing plants has an impact on Rowley Shoals.